A Framework for Analyzing the Ethics of Disclosing Genetic Research Findings. Issue 2 (June 2014) - Eckstein, Lisa; Garrett, Jeremy R.; Berkman, Benjamin E.
<x xml:space="preserve">Abstract</x> Whether researchers have an obligation to disclose secondary genetic research findings, and, if so, in what circumstances, remains a matter of heated debate. This paper suggests that much of this confusion is definitional or conceptual in nature. That is, there is significant variability in the way that threshold terms and concepts such as "incidental, " "analytic validity, " "clinical validity, " "clinical relevance, " "clinical utility, " "clinical significance, " and "actionability, " are used in the literature, which is impeding efforts to clarify the scope of an obligation to return findings. This paper analyzes the definitional muddle underlying the debate about returning genetic research findings, first, to explain the range of definitions being used in this debate. We go on to propose that, underlying all the seeming confusion and disagreement, three central and widely agreed upon concepts are at work in this debate — validity, value, and volition. Refocusing attention on these core concepts, and their appropriate conceptualizations, can produce a more productive debate regarding the return of genetic research findings.